Computer-aided instruction on social studies student’s achievement and retention - Uwaifo, Roseline Osayi; Osah, Mark Igho; Obro, Sunday (Intelektual Pustaka Media Utama, 2025)
The study explored innovative instructional strategy: effect of computer-aided instruction on social studies students’ achievement and retention outcome. The study was an experimental study. The sample of the study was 180 students. The instrument used for the study was the scholarly achievement test (SAT). Descriptive statistics were utilized to provide answers to the research questions and analysis of variance (ANOVA) was employed to test the hypotheses. The result established that computer-aided instruction (CAI) impacted social studies students’ achievement. The result also established a significantly improved retention of students instructed with CAI and that gender-wise, female students achieved better than the male students in the university. It was suggested that teachers should incorporate CAI into social studies lessons. Educators should be educated on the use of CAI.